Comparison of the Kinetic Promoter Piperazine and Carbonic Anhydrase for CO2 Absorption. (July 2017) - Gladis, Arne; Gundersen, Maria T.; Thomsen, Kaj; Fosbøl, Philip L.; Woodley, John M.; von Solms, Nicolas
Abstract: Kinetic promoter that enhance the reaction kinetics with CO2 are enabling the use of the low heat of reaction of slow absorbing solvents like MDEA. Mass transfer experiments with 30 wt% MDEA promoted by either by 1.7 and 8.5 g/L enzyme carbonic anhydrase (CA) or 5 wt% piperazine (PZ) where conducted in a wetted wall column apparatus at 298, 313 K and 328 for different solvent loadings. The mass transfer of PZ promoted solvents was strongly influenced by the solvent loading as it was steeply decreasing for all temperatures; the temperature was also influencing the mass transfer, but the extent was dependent on the solvent loading. CA promoted solvent mass transfer characteristics showed less dependency on the solvent loading and temperature. Lower enzyme concentrations were found to be much slower than MDEA/PZ solvents, whereas high enzyme concentrations might be as efficient in capturing CO2 as a 30 wt% MDEA/5 wt%PZ mixture in terms of overall mass transfer, considering change of mass transfer due to solvent loading over the height of a column.